Laminated film
Patent Information
- Application Number
- JP2024028295
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-31
- Filing Date
- 2024-02-28
- Publication Date
- 2025-02-13
AI Technical Summary
【0009】 本発明により、積層フィルムとして用いるために必要な機械特性を備え、かつ、布等に対する密着性および触感に優れ、さらに、積層フィルムをロールtoロールで加工するときに搬送ロール等への貼り付きを抑制する積層フィルムを提供することができる。
Smart Images

Figure 2025021407000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated film that has excellent adhesion and tactile feel to materials having an uneven surface, such as cloth or nonwoven fabric. [Background technology]
[0002] In recent years, there has been a demand for standalone films that have the mechanical properties necessary for use as a film and also have other functions. For example, in the field of medical and sanitary materials, there is a demand for films that have the mechanical properties of a film, as well as surface irregularities, elasticity, and flexibility, and that have excellent adhesion and tactile feel to materials such as cloth and nonwoven fabrics (hereinafter sometimes referred to as cloth, etc.).
[0003] To date, various developments have been made to improve these properties, and for example, Patent Document 1 discloses a film in which the surface is formed of particles and an adhesive resin, and the particles are placed on the surface of the layer of adhesive resin. By adopting such an embodiment, when the surface is touched, the particles suppress contact between the adhesive layer and the skin, improving the tactile feel of the film. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-31596 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, while the technology of Patent Document 1 can achieve both good adhesion to fabrics and good handleability, there is a problem in that the outermost surface becomes an adhesive layer, which reduces the tactile feel.
[0006] The present invention aims to overcome the drawbacks of the conventional technology and to provide a laminated film that has the mechanical properties required for use as a laminated film, has excellent adhesion to fabrics and the like and a good feel, and is capable of preventing adhesion to conveying rolls and the like when the film of the present invention is processed by roll-to-roll processing. [Means for solving the problem]
[0007] In order to solve the above problems, the present invention comprises the following configuration. (1) A laminate film having different peel strengths to fabric on both sides, characterized in that when the outermost layer on the side having a relatively high peel strength to fabric is Layer A, Layer A contains resin and particles, the skewness (Rsk) which is the surface roughness of Layer A is 1.00 or more and 4.00 or less, and the exposure failure rate of particles is 0% or more and 30% or less. (2) The laminate film according to (1), wherein the exposed ratio of particles in the layer A is 50% or more and 80% or less.
[0008] (3) The laminate film according to (1) or (2), characterized in that, when the thickness of the A layer is X μm and the average particle size of the particles contained in the A layer is Y μm, Y / X is 5.0 or more and 20.0 or less. (4) The laminate film according to (1), wherein the average particle size of the particles contained in the layer A is 20 um to 80 um. (5) The laminate film according to (1), wherein the content of particles contained in the layer A is 30% by mass to 60% by mass. Effect of the Invention
[0009] The present invention can provide a laminate film that has the mechanical properties required for use as a laminate film, has excellent adhesion to fabrics and the like and a good feel, and further, is inhibited from sticking to transport rolls and the like when the laminate film is processed by roll-to-roll. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is an enlarged top view of a laminate film according to one embodiment of the present invention, observed from the layer A side. [Diagram 2] 2 is a cross-sectional view of the laminated film taken along the line II' of FIG. [Diagram 3] 2 is an image of the convex portions of the laminate film of the present invention observed from the layer A side. [Figure 4] 1 is an image of the exposed part of the particle of the laminate film of the present invention observed from the layer A side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The laminate film of the present invention is a laminate film having different peel strengths to fabric on both sides, and when the outermost layer on the side having a relatively greater peel strength to fabric is Layer A, Layer A contains resin and particles, has a skewness (Rsk) which is the surface roughness of Layer A of 1.00 or more and 4.00 or less, and has a particle exposure failure rate of 0% or more and 30% or less.
[0012] A film refers to a sheet-like molded body whose main component is a thermoplastic resin, and a laminated film refers to a film having multiple layers with different compositions. Note that "whose main component is a thermoplastic resin" means that the film contains more than 50% by mass and up to 100% by mass of thermoplastic resin among all the components that make up the film.
[0013] It is important that the laminated film of the present invention has different peel strengths to fabric on both sides. "Different peel strengths to fabric on both sides" means that the difference between the peel strength to fabric on the side with a relatively high peel strength to fabric and the peel strength to fabric on the opposite side is 0.05 N / cm or more. In this case, the outermost layer on the side with a relatively high peel strength to fabric is layer A, and the outermost layer on the opposite side is layer B.
[0014] The peel strength to cloth can be measured according to the method specified in JIS Z 0237:2009. Specifically, a rectangular laminated film sample of 10 mm x 100 mm is obtained, the obtained laminated film sample is placed on a polyester white cloth (hereinafter, sometimes simply referred to as cloth) conforming to JIS L 0803:2011, and a laminating roller with a load of 1 kg is moved back and forth once to bring the two into close contact. Thereafter, the laminated film sample is peeled from the short side at a pulling speed of 300 mm / min, and the peel strength is measured.
[0015] The method of forming the laminated film in a form in which the peel strength against fabric is different on both sides is not particularly limited as long as it does not impair the effects of the present invention. For example, a method in which one arbitrarily selected outermost layer and the other outermost layer have different compositions can be mentioned. More specifically, the method is a method in which the content of the adhesive resin (described later) in one arbitrarily selected outermost layer is different from the content of the adhesive resin in the other outermost layer. In such a form, the surface on the outermost layer side with a higher content of adhesive resin is usually the "surface with a relatively high peel strength against fabric", the outermost layer with a higher content of adhesive resin is layer A, and the outermost layer on the opposite side is layer B. In this case, the difference between the content of the adhesive resin in layer A and the content of the adhesive resin in layer B can be increased to increase the difference in peel strength against fabric on both sides.
[0016] The content of the adhesive resin in the A layer refers to the content (mass%) of the adhesive resin when the total components of the A layer are taken as 100 mass%, and the content of the adhesive resin in the B layer is interpreted in the same manner. In this case, the B layer does not necessarily need to contain an adhesive resin. Although the adhesive resin can improve the adhesion to the cloth, it is inferior in mechanical strength to the resin that can be used in the B layer described later. Therefore, by adopting such an embodiment, it is possible to easily achieve both the mechanical properties of the laminated film and the adhesion to the cloth. In this case, another layer may be present between the A layer and the B layer within a range that does not impair the effects of the present invention.
[0017] It is important that the surface of the layer A of the laminate film of the present invention contains a resin and particles. From the viewpoints of adhesion to cloth and the like and productivity, the resin in the layer A preferably contains a thermoplastic elastomer and an adhesive resin.
[0018] Thermoplastic elastomer refers to a high molecular weight material that has rubber elasticity at 25°C due to having a hard segment phase and a soft segment phase, while at the same time, the hard segment phase exhibits fluidity in the temperature range of 100°C to 300°C, which is the general thermoplastic molding temperature range, and thus allows molding processing similar to that of general thermoplastic resins. Examples of thermoplastic elastomers that can be used for the A layer include polyester-based elastomers, polyolefin-based elastomers, polyamide-based elastomers, polyurethane-based elastomers, styrene-based elastomers, and polyacrylic-based elastomers, which can be used alone or in combination. Among them, it is preferable to use styrene-based elastomers from the viewpoint of adhesion of the obtained laminated film to cloth, etc.
[0019] Examples of styrene-based elastomers include styrene-butadiene block copolymers, styrene-ethylene propylene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylenebutylene-styrene block copolymers, and styrene-ethylenepropylene-styrene block copolymers.
[0020] The adhesive resin means a rosin-based resin, a terpene-based resin, a petroleum-based resin, or a mixture of these resins. When such an adhesive resin is mixed with a polymeric material, it exhibits adhesiveness due to a plasticizing effect. Therefore, when layer A contains more adhesive resin than layer B, the adhesion between layer A and a cloth or the like is improved. "Layer A contains more adhesive resin than layer B" means that the content (mass%) of adhesive resin in layer A is greater than the content (mass%) of adhesive resin in layer B.
[0021] Rosin resin refers to a resin whose main component is rosin acid (abietic acid, palustric acid, isopimaric acid, etc.). Here, "whose main component is rosin acid" means that the adhesive resin contains more than 50% by mass and up to 100% by mass of rosin resin among all the components that make up the adhesive resin.
[0022] The rosin-based resin that can be used in the laminated film of the present invention can be obtained, for example, as a residue remaining after collecting balsams such as pine resin, which is the sap of plants of the Pinaceae family, and distilling turpentine essential oil. Specific examples of the rosin-based resin include unmodified rosins such as gum rosin, wood rosin, and tall oil rosin, and modified rosins obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, or other chemical modification.
[0023] The petroleum-based resin refers to a resin obtained by polymerizing a part of the by-product oil of naphtha cracking (highly unsaturated dienes, etc.). Examples of the petroleum-based resin that can be used in the laminated film of the present invention include aliphatic petroleum-based resins, aromatic petroleum-based resins, aliphatic / aromatic copolymer petroleum-based resins, and hydrogenated products thereof.
[0024] Terpene resins refer to polymers of terpene monomers, copolymers of terpene monomers and other monomers, and derivatives thereof. Examples of terpene resins include α-pinene polymers, β-pinene polymers, dipentene polymers, and the like, as well as modified terpene resins such as terpene phenol resins, styrene-modified terpene resins, and hydrogenated terpene resins.
[0025] The particles contained in the A layer are not particularly limited as long as they do not impair the effects of the present invention, and may be either inorganic particles or organic particles, or may be a combination of organic particles and inorganic particles, or a combination of multiple types of inorganic particles or multiple types of organic particles. Examples of inorganic particles include silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, zirconium oxide, and titanium oxide. Examples of organic particles that can be used in the laminated film of the present invention include polyethylene resin, polyolefin resin, acrylic resin, urethane resin, styrene resin, urea resin, phenol resin, and epoxy resin.
[0026] The shape of the particles is not particularly limited as long as it does not impair the effects of the present invention, and may be any of spherical, lumpy, rod-like, flat, etc., and different shapes can be used in combination as necessary, but spherical is preferable in terms of the feel of the resulting laminated film.
[0027] The average particle size of the particles contained in the A layer is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 20 μm or more and 80 μm or less, and more preferably 40 μm or more and 80 μm or less. If the average particle size of the particles in the A layer is 20 μm or more, it is easy to form unevenness on the surface of the A layer, and it is easy to improve the tactile feel of the A layer surface. On the other hand, if the average particle size of the particles in the A layer is 80 μm or less, it is possible to reduce the particles from falling off from the A layer.
[0028] The average particle size of the particles in layer A can be determined by the following procedure. The laminated film is cut to 10 cm x 10 cm and immersed in toluene for 30 minutes or more. Next, layer B is taken out and the particle size distribution of the toluene solution in which layer A has been melted is measured under the following conditions. The average diameter obtained from the measurement results is taken as the average particle size of the particles. The measurement conditions are as follows. The measurement device used is a Shimadzu SALAD-7100, and the cell used is a batch cell. The refractive index is 1.70-0.20.
[0029] In the laminated film of the present invention, the content of particles contained in the A layer is preferably 30% by mass or more and 60% by mass or less, more preferably 30% by mass or more and 50% by mass or less. If the content of particles contained in the A layer is 30% by mass or more, unevenness can be easily formed on the surface of the A layer, and the contact area between the user's skin and the adhesive resin is reduced, so that a laminated film with excellent tactile feel can be obtained. On the other hand, if the content of particles contained in the A layer is 60% by mass or less, the adhesion of the obtained laminated film to cloth, etc. is improved, and if the content of particles contained in the A layer is 50% by mass or less, the adhesion of the obtained laminated film to cloth, etc. is further improved. The "content of particles contained in the A layer" refers to the amount of particles in the A layer when all components constituting the A layer are 100% by mass.
[0030] The content of particles contained in the A layer can be measured by the following procedure. First, the laminate film is cut to 10 cm x 10 cm and the mass is measured. Furthermore, the cut laminate film is immersed in toluene for 30 minutes or more, taken out, and the mass of the film after drying is measured. The difference in mass before and after immersion in toluene is the mass of the A layer. Next, the particles are taken out of the toluene solution, and the mass of the particles after drying is measured. The value of (mass of particles) / (mass of A layer) is the content of particles contained in the A layer. Note that, as long as the particles are a component that dissolves in toluene, the organic solvent in which the laminate film is immersed can be appropriately replaced with another one. It is important that the skewness (Rsk), which is the surface roughness of the A layer in the laminate film of the present invention, is 1.00 or more and 4.00 or less. Rsk is preferably 1.80 or more and 4.00 or less, and more preferably 2.00 or more and 4.00 or less. If Rsk is 1.00 or more, a laminate film that combines cloth adhesion and tactile feel can be obtained. If Rsk is 4.00 or less, the falling off of particles in the A layer can be reduced.
[0031] The touch feeling referred to here means the touch feeling when touching the A layer side of the laminated film, which can be evaluated using the friction coefficient of the A layer as an index. More specifically, the smaller the friction coefficient of the A layer, the less sticky it feels when touched and the better the touch feeling. The friction coefficient of the A layer can be measured with a known roughness / friction feeling tester (e.g., KES-SESRU, manufactured by Kato Tech Co., Ltd.), and the measurement conditions when using this device are as shown in the examples.
[0032] The skewness (Rsk) on the surface of the A layer can be adjusted by the average particle size, particle content, and coating amount of the A layer forming composition. Specifically, Rsk can be increased by increasing the average particle size, increasing the particle content, and decreasing the coating amount of the A layer forming composition. Rsk can also be decreased by decreasing the average particle size, decreasing the particle content, and increasing the coating amount of the A layer forming composition.
[0033] Skewness (Rsk) can be measured by the following procedure. First, the surface of layer A is observed with a laser microscope at a magnification where 20 to 40 particles that form convex parts on the surface of layer A are visible on the screen. Next, the surface roughness of the captured image is obtained using the measurement function of the laser microscope. Rsk is calculated for surface roughness using a formula based on JIS B0601:2001 with no cutoff.
[0034] It is important that the particle exposure failure rate in the laminated film of the present invention is 0% or more and 30% or less. The particle exposure failure rate indicates the ratio of the number of particles contained in the A layer that are not exposed from the adhesive layer. The particle exposure failure rate is preferably 0% or more and 20% or less, more preferably 0% or more and 10% or less, and particularly preferably 4% or more and 10% or less. If the particle exposure failure rate is 0% or more, the adhesion of the obtained laminated film to cloth, etc. is improved. If the particle exposure failure rate is 30% or less, the laminated film can be prevented from sticking to a transport roll, etc., when being transported.
[0035] The exposure failure rate of the particles can be adjusted by the coating amount and viscosity of the composition for forming the A layer in the coating method, after adopting a coating method for forming an adhesive layer in the manufacturing method. Specifically, the exposure failure rate of the particles can be reduced by reducing the coating amount and viscosity of the composition for forming the A layer. In addition, the exposure failure rate of the particles can be increased by increasing the coating amount and viscosity of the composition for forming the A layer.
[0036] The particle exposure failure rate can be measured by the following method. First, the surface of the A layer of the laminated film is observed with a scanning electron microscope at a magnification where 5 to 10 particles are visible on the screen. Next, the number of all particles in the A layer on the screen and the number of particles whose apex parts are not exposed are counted, and the particle exposure failure rate is calculated as (number of particles whose apex parts are not exposed) / (total number of particles in the A layer) x 100. The measurement was performed 10 times at different measurement locations on the A layer of the laminated film, and the average value of the 10 obtained exposure failure rates was calculated. If the difference between the surface state of the exposed particles and the surface state of the adhesive layer covering the particles is not clear, the contrast or brightness may be adjusted or binarized as necessary. The particle exposure rate in the laminated film of the present invention is preferably 50% or more and 80% or less. The particle exposure rate indicates the ratio of the area of the particles contained in layer A that are exposed from the adhesive layer. The particle exposure rate is more preferably 60% or more and 80% or less. If the particle exposure rate is 50% or more, the contact area between the user's skin and the adhesive resin is smaller, so that a laminated film with excellent tactile feel can be obtained. If the particle exposure rate is 80% or less, the adhesion of the obtained laminated film to cloth, etc. is improved.
[0037] The particle exposure rate can be adjusted by the coating amount and viscosity of the A layer forming composition in the coating method, after adopting a coating method for forming an adhesive layer in the manufacturing method. Specifically, the particle exposure rate can be increased by reducing the coating amount of the A layer forming composition or decreasing the viscosity. In addition, the particle exposure rate can be decreased by increasing the coating amount of the A layer forming composition or increasing the viscosity.
[0038] The method for measuring the particle exposure rate will be described with reference to FIG. 4, which is an image of the convex portion of the laminated film of the present invention observed from the A layer side. First, the surface of the A layer is observed with a laser microscope at a magnification where a single convex portion that is independent on the A layer surface and has a clear difference between the surface state of the exposed particle and the surface state of the adhesive layer covering the particle is captured in the screen. If the difference between the surface state of the exposed particle and the surface state of the adhesive layer covering the particle is not clear, the contrast and brightness are adjusted as necessary. Next, the length of the longest straight line (9 in FIG. 4) that passes through the exposed part of the particle is measured using the measurement function of the laser microscope. Furthermore, the length of the longest straight line (10 in FIG. 4) that is perpendicular to the measured straight line is measured, and the area of the circle calculated with the radius being 1 / 2 the average value of the lengths of these two points is taken as the area of the exposed part. In addition, the area of the circle calculated with the radius being 1 / 2 the average particle size of the particle is taken as the average area of the particle. The particle exposure rate is calculated as (area of the exposed part) / (average area of the particle)×100. The same measurement was carried out 10 times at different measurement locations, and the average of the 10 values was calculated. The average particle size of the particles is measured in the "(3) Average particle size of particles in layer A" section described in the Examples section below.
[0039] In the laminate film of the present invention, when the thickness of layer A is X μm and the average particle size of the particles contained in layer A is Y μm, Y / X is preferably 5.0 to 20.0, and more preferably 10.0 to 20.0.
[0040] By setting Y / X to 5.0 or more, a laminate film with excellent tactile sensation can be obtained. By setting Y / X to 20.0 or less, it is possible to reduce the falling off of particles in layer A and to set the adhesion to cloth, etc. within a preferred range.
[0041] Here, the thickness of layer A refers to the thickness of the part of layer A where there are no particles, and can be determined by the following method. The laminated film of the present invention was cut parallel to the thickness direction using a microtome with a knife inclination angle of 3°. Next, the cross section of layer A was observed using a scanning electron microscope, and the thickness of layer A was measured at the part where no particles were present using the length measurement function of the microscope. The measurement was performed 10 times with different sampling positions, and the average thickness of layer A obtained was calculated.
[0042] Layer A may contain components other than those described above, provided that the effects of the present invention are not impaired. Examples of such components include lubricants, antioxidants, UV stabilizers, matting agents, antibacterial agents, deodorants, weather resistance agents, antioxidants, ion exchange agents, color pigments, and dyes.
[0043] Layer B in the laminated film of the present invention is not particularly limited, but is preferably composed mainly of a thermoplastic resin such as a polyester resin, a polyolefin resin, or a polystyrene resin. Here, "composed mainly of a thermoplastic resin" means that the layer contains more than 50% by mass and not more than 100% by mass of a thermoplastic resin when the total resin components constituting the layer are taken as 100% by mass.
[0044] The polyester resin refers to a homopolyester or copolymer polyester which is a polycondensation product of a dicarboxylic acid component skeleton and a diol component skeleton. Here, examples of homopolyester include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, poly-1,4-cyclohexanedimethylene terephthalate, and polyethylene diphenylate. The copolymer polyester refers to a polycondensation product consisting of at least two or more components selected from the following components having a dicarboxylic acid skeleton and components having a glycol skeleton.
[0045] Examples of components having a dicarboxylic acid skeleton include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, adipic acid, sebacic acid, dimer acid, cyclohexanedicarboxylic acid, and ester derivatives thereof.
[0046] Examples of components having a glycol skeleton include ethylene glycol, 1,2-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, diethylene glycol, polyalkylene glycol, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, isosorbate, 1,4-cyclohexanedimethanol, and spiroglycol.
[0047] Polyolefin resins are homopolymers of olefins such as ethylene and propylene, or copolymers containing multiple olefins. Examples of homopolymers of olefins include polyethylene and polypropylene. Examples of copolymers containing olefins include ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, and ethylene-vinyl chloride copolymers.
[0048] The polystyrene resin refers to a homopolymer of styrene or a copolymer containing styrene. An example of the homopolymer of styrene is polystyrene. An example of the copolymer containing styrene is acrylonitrile butanediene styrene.
[0049] Examples of homopolymers of olefins include polyethylene, polypropylene, etc. Examples of copolymers with different polyolefins include ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, ethylene-vinyl chloride copolymer, etc.
[0050] Among them, from the viewpoint of easily setting the Young's modulus of the obtained laminated film in the preferred range described later, it is preferable that the B layer in the laminated film of the present invention contains a polyester resin as the main component. In addition, a combination of multiple other resins may be used within a range that does not impair the effects of the present invention.
[0051] Furthermore, when the laminated film of the present invention is applied to disposable products such as sanitary materials, it is preferable to use a biopolyethylene terephthalate film made from terephthalic acid derived from biomass raw materials or ethylene glycol derived from bioethanol, or a biodegradable polylactic acid film.
[0052] Layer B may contain a filler as long as it does not impair its effect. The filler refers to a substance added to improve various properties, or an inactive substance added for the purpose of increasing the amount, increasing the volume, or reducing the cost of the product. The type of filler is not particularly limited as long as it does not impair the effects of the present invention, and inorganic fillers and / or organic fillers can be used. In addition, as long as it does not impair the effects of the present invention, the filler may be one type or a mixture of multiple types. From the viewpoint of easily setting the Young's modulus of the obtained laminated film to a preferred range described later, the filler is preferably an inorganic filler, and it is more preferable to use at least one type of metal carbonates such as calcium carbonate, barium carbonate, and magnesium carbonate, metal sulfates such as barium sulfate and calcium sulfate, metal oxides such as titanium oxide and zinc oxide, silicon oxide (silica), aluminosilicates, mica, talc, kaolin, clay, and composite oxides such as montmorillonite, and from the viewpoint of versatility and cost, it is even more preferable to use calcium carbonate alone or in combination with other fillers.
[0053] The content of the filler in the B layer is not particularly limited as long as it does not impair the effects of the present invention, but from the viewpoint of easily setting the Young's modulus of the obtained laminated film to a preferred range described later, when the total resin components of the B layer are taken as 100 parts by mass, it is preferably 5 parts by mass or more and 200 parts by mass or less, and more preferably 10 parts by mass or more and 150 parts by mass or less. In addition, the B layer may contain components other than the above-mentioned components within a range that does not impair the effects of the present invention. Examples of such components include lubricants, antioxidants, ultraviolet stabilizers, matting agents, antibacterial agents, deodorants, weather resistance agents, antioxidants, ion exchange agents, coloring pigments, and dyes.
[0054] The structure of the laminate film of the present invention will be described with reference to the structure shown in Figs. 1 and 2 (two-layer structure of two types) as an example, but the layer structure of the laminate film of the present invention is not limited to this as long as the effect of the laminate film is not impaired. Fig. 1 is an enlarged top view of a laminate film according to one embodiment of the present invention observed from the layer A side, and Fig. 2 is a cross-sectional view taken along the line I-I' of the laminate film of Fig. 1. The laminate film 1 of the present invention has a two-layer structure consisting of two layers, layer A 2 and layer B 3, and layer A 2 is composed of particles 4 and resin 5. On the surface of layer A 1, protrusions 6 are formed by particles 4 protruding from layer A.
[0055] Figure 3 shows a scanning electron microscope photograph taken when measuring the rate of particle exposure failure. On the surface of layer A in the laminated film, there are particles whose apex surfaces are exposed (shown by symbols 7-1, 7-2, and 7-3) and particles whose apex surfaces are not exposed (shown by symbols 8-1, 8-2, and 8-3).
[0056] A preferred method for producing the laminated film of the present invention is to apply a composition for obtaining layer A dissolved in a known solvent to another layer such as layer B and dry it (hereinafter, sometimes referred to as a coating method). By using the coating method, the composition for obtaining layer A is applied to another layer such as layer B, and the solution of the adhesive layer repels the particles due to leveling, so that a desired particle exposure rate can be easily obtained.
[0057] Specifically, the following coating method can be used. First, to obtain a composition for obtaining the A layer, the components for obtaining the A layer other than the particles are dissolved in a known solvent (e.g., toluene, methyl ethyl ketone (MEK), etc.), and then the particles are added (hereinafter referred to as the A layer solution). Next, the A layer solution containing the particles is applied onto the B layer, and the solvent is dried and removed in an oven to form the A layer. The method for applying the A layer solution is not particularly limited, but for example, a bar coating method, a comma coating method, a slit die coating method, a reverse roll coating method, a knife coating method, a gravure coating method, etc. can be suitably used. EXAMPLES
[0058] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto in any way.
[0059] [Measurement and evaluation methods] The measurements and evaluations shown in the examples were carried out under the following conditions.
[0060] (1) Rsk (skewness) for A tier The A layer side of the laminated film was observed with a laser microscope (VK-X100, Keyence Corporation) at a magnification of 20 times, and an observation image was obtained. The surface roughness of the obtained observation image was calculated using the attached analysis application. Specifically, the entire surface of the observation image was designated as the evaluation area, and Rsk was calculated using a calculation formula conforming to JIS B0601:2001 without cutoff. The same measurement was performed 10 times by changing the observation position, and the average value of the 10 obtained surface roughness values was taken as the Rsk of the A layer.
[0061] (2) Particle exposure failure rate The surface of the A layer in the laminated film was observed with a scanning electron microscope at a magnification where 5 to 10 particles were visible on the screen. Next, the number of all particles in the A layer on the screen and the number of particles whose apex surface was not exposed from the A layer were measured, and the particle exposure failure rate was calculated as (number of particles whose apex surface was not exposed from the A layer) / (number of all particles in the A layer) x 100. The measurement was performed 10 times at different measurement locations, and the average value of the 10 exposure failure rates was calculated. If the difference between the surface state of the exposed particles and the surface state of the adhesive layer covering the particles was not clear, the contrast and brightness were adjusted or binarized as necessary. Note that particles whose portions other than the apex portion are exposed from the A layer but whose apex portion is not exposed from the A layer are not considered to be particles whose apex surface is exposed from the A layer.
[0062] (3) Average particle size of particles contained in layer A The laminated film was cut to a size of 10 cm x 10 cm and immersed in toluene for 30 minutes or more. Next, layer B was taken out, and the particle size distribution of the toluene solution in which layer A had melted was measured under the following conditions. The average diameter obtained from the measurement results was taken as the average particle size of the particles. <Measurement conditions> Measurement equipment: Shimadzu SALAD-7100 Cell: Batch cell Refractive index: 1.70-0.20 Similar measurements were carried out 10 times at different measurement locations, and the average of the 10 values obtained was taken as the average particle size (μm) of the particles in layer A.
[0063] (4) Particle exposure rate The surface of layer A was observed with a laser microscope (VK-X100, Keyence Corporation) at a magnification where one convex part, which was independent on the surface of layer A and had a clear difference between the surface state of the exposed particle and the surface state of the adhesive layer covering the particle, was captured on the screen. Next, the length of the exposed part with the longest straight line was measured using the measurement function of the laser microscope. Furthermore, the length of the exposed part of the straight line perpendicular to the measured straight line was measured, and the area of the exposed part was determined as the area of a circle with a radius of 1 / 2 the average length of the two points. In addition, the area of a circle with a radius of 1 / 2 the average particle diameter of the particles was determined as the average area of the particles. Then, the exposed rate of the particles was determined as (area of exposed part) / (average area of particles)×100. The same measurement was performed 10 times at different measurement locations, and the average value of the 10 values obtained was calculated.
[0064] (5) Mass of layer A and particle content in layer A The laminated film was cut into 10cm x 10cm pieces and the mass was measured. The cut laminated film was then immersed in toluene for 30 minutes or more, removed, and dried, after which the mass of the film was measured. The difference in mass before and after immersion in toluene was then calculated, and this was taken as the mass of layer A. Furthermore, the particles in the toluene solution were removed, and the mass of the particles after drying was measured, and the value of (mass of particles) / (mass of layer A) was calculated, and this was taken as the content of particles contained in layer A.
[0065] (6) Thickness of layer A The laminated film was cut parallel to the thickness direction using a microtome with a knife inclination angle of 3°. Next, the cross section of layer A was observed using a scanning electron microscope, and the thickness of layer A was measured using the length measurement function of the microscope at a point where no particles were present. After that, the same measurement was performed nine times by changing the sampling position, and the average thickness of layer A at a total of 10 points was taken as the thickness (μm) of layer A of the laminated film.
[0066] (7) Thickness of layer B The laminated film was cut parallel to the thickness direction using a microtome with a knife inclination angle of 3°. Next, the cross section of layer B was observed using a scanning electron microscope, and the thickness of layer B was measured using the length measurement function of the microscope at a location where no particles were present. After that, the same measurement was performed nine times by changing the sampling position, and the average thickness of layer B at a total of 10 locations was taken as the thickness (μm) of layer B of the laminated film.
[0067] (8) Peel strength of layer A to fabric A rectangular laminated film sample of 10 mm (width direction) x 100 mm (length direction) was obtained, and the laminated film sample was placed on a polyester white cloth (hereinafter, simply referred to as cloth) conforming to JIS L 0803:2011, and a laminating roller with a load of 1 kg was moved back and forth once to bring them into close contact with each other. The laminated film sample was then peeled off from the short side at a pulling speed of 300 mm / min, and the peel strength to the cloth was measured by the method specified in JIS Z 0237:2009. The same measurement was performed five times, and the average value of the obtained values was taken as the peel strength to the cloth (N / cm). The peel strength was measured on each side of the laminated film sample, and the outermost layer on the side with a peel strength to the cloth of 0.05 N / cm or more was taken as layer A.
[0068] (9) Friction coefficient of layer A The laminated film was cut into a square sample measuring 50 mm (width direction) x 150 mm (length direction). The coefficient of friction was measured under the following conditions using a roughness / friction tester (KES-SESRU, manufactured by Kato Tech Co., Ltd.). Measurements were taken 5 times at different measurement positions, and the average value was used as the coefficient of friction of layer A. <Measurement conditions> Friction terminal type: Fingerprint type Friction terminal load: 25gf Speed: 5mm / sec.
[0069] (10) Adhesion to SUS plate The laminated film was cut into a square of 50 mm (width direction) x 150 mm (length direction) to prepare a sample for measurement. The sample and the SUS plate were overlapped so that the A layer surface was in contact with the SUS plate, and pressure was applied at 25 degrees, 1 MPa, and 1 minute. The state of adhesion between the sample and the SUS plate after pressure was confirmed.
[0070] [Resin components contained in layer A] (A1) Adhesive layer solution (a mixture of toluene, styrene-isoprene-styrene copolymer, and adhesive resin (petroleum resin, terpene resin, and terpene phenol resin), solid content: 50% by mass, GR-1025M-1, manufactured by Big Technos Co., Ltd.) (A2) Adhesive layer solution (a mixture of toluene, styrene-isoprene-styrene copolymer, and adhesive resin (terpene resin, rosin resin, and phenol resin), solid content: 50 mass%, GR-1045M-1, manufactured by Big Technos Co., Ltd.).
[0071] [Dilution solvent for the resin component contained in layer A] (B1) Toluene [Particles contained in layer A] (C1) Polyethylene particles (XM-330, average particle size 65 μm, manufactured by Mitsui Chemicals, Inc.) (C2) Polyethylene particles (XM-220, average particle size 32 μm, manufactured by Mitsui Chemicals, Inc.) [Color pigments for layer A] (D1) Titanium oxide (R-101, manufactured by DuPont). [B layer] (PET) Polyester film (6CF56, manufactured by Toray Industries, Inc.).
[0072] Example 1 The adhesive layer resin, dilution solvent, particles and color pigment were mixed in the ratio shown in Table 1 to obtain a solution for forming layer A. Next, the thickness of the laminated film was measured. 2 The mass of the A layer per unit area (hereinafter, including the table, simply referred to as the "mass of the A layer") is 10 g / m 2The solution was applied onto the film of layer B using a bar coater so that the film was coated with the solution and dried at 120° C. for 1 minute to obtain a laminated film. The physical properties and evaluation results of the obtained laminated film are shown in Table 2.
[0073] (Examples 2 to 10, Comparative Examples 1 to 2) A laminate film was obtained in the same manner as in Example 1, except that the composition of the solution for forming layer A and layer B were as shown in Table 1. The physical properties and evaluation results of the obtained laminate film are shown in Table 2.
[0074] As shown in Table 2, in Comparative Example 1, the particle exposure failure rate of the A layer was high, so the film adhered to the SUS plate and had poor handling properties. In Comparative Example 2, the Rsk was low, so the film adhered to the cloth poorly.
[0075] [Table 1]
[0076] [Table 2] [Industrial Applicability]
[0077] The present invention provides a laminated film that has the mechanical properties required for use as a laminated film, has excellent adhesion and tactile feel to fabrics, and is less susceptible to particle falling off or burial during storage and use. The laminated film of the present invention can be preferably used for applications requiring adhesion and handling to fabrics, for example, medical and sanitary materials such as bed sheets, pillow covers, and back sheets of absorbent articles such as sanitary napkins and disposable diapers. In addition, since it has the same handling properties as a hook-and-loop fastener and can be repeatedly attached to any object to be attached, as long as it is fabric, and has a wide range of options for the object to be attached, it can be preferably used as a replacement for a hook-and-loop fastener. [Explanation of symbols]
[0078] 1: Laminated film 2:A layer 3:B layer 4: Particles contained in layer A 5: Resin 6: Convex part 7-1: Particles whose surface is exposed from layer A 7-2: Particles whose surface is exposed from layer A 7-3: Particles whose surface is exposed from layer A 8-1: Particles whose surface is not exposed from layer A 8-2: Particles whose surface is not exposed from layer A 8-3: Particles whose surface is not exposed from layer A 9: The longest straight line through the exposed part of the particle 10: The longest straight line that intersects with line 9 and passes through the exposed part of the particle
Claims
1. A laminate film having different peel strengths to fabric on both sides, with the outermost layer on the side having a relatively high peel strength to fabric being Layer A, characterized in that Layer A contains resin and particles, the skewness (Rsk) which is the surface roughness of Layer A is 1.00 or more and 4.00 or less, and the exposure failure rate of particles is 0% or more and 30% or less.
2. 2. The laminated film according to claim 1, wherein the exposed ratio of the particles in the layer A is 50% or more and 80% or less.
3. 3. The laminate film according to claim 1, wherein, when the thickness of the A layer is X μm and the average particle size of the particles contained in the A layer is Y μm, Y / X is 5.0 or more and 20.0 or less.
4. 2. The laminated film according to claim 1, wherein the average particle size of the particles contained in the layer A is from 20 um to 80 um.
5. 2. The laminated film according to claim 1, wherein the content of particles contained in the layer A is 30% by mass to 60% by mass.
Citation Information
Patent Citations
Film
JP2019031596A